Komunikasi Dakwah dalam Sastra - Mochamad Aris Yusuf (Jurnal Indonesia Sosial Teknologi, 2022)
Essays are inspirational works that are communicated by their authors, as in the book Tak Ada Ikan Asin di Lautan, which tells the story of the wisdom of life taken from the basis of the Koran. The purpose of this study is to explain the purpose of da'wah communication in the essay book Tak Ada Ikan Asin di Lautan by Edi Ah Iyubenu. This research method uses a qualitative descriptive method, obtained with a content analysis approach, through data collection techniques such as library research. The findings in this study are three identical techniques with da'wah, namely: 1) informative communication, informing the reader of the concept of piety in the author's idea of ​​​​Edi Ah Iyubenu 2) persuasive communication, changing the reader's belief with a motivational approach 3) instructive communication, ordering the reader if something is bad found to be better left. So it can be concluded that the achievement of da'wah communication carried out by Edi Ah Iyubenu, gained knowledge that could be realized by the reader.